Social Media Recruitment Strategies to Recruit Pregnant Women Into a Longitudinal Observational Cohort Study: Usability Study - Chloe Pekarsky; Janice Skiffington; Lara M Leijser; Donna Slater; Amy Metcalfe (JMIR Publications, 2022)
BackgroundUse of social media for study recruitment is becoming increasingly common. Previous studies have typically focused on using Facebook; however, there are limited data to support the use of other social media platforms for participant recruitment, notably in the context of a pregnancy study. ObjectiveOur study aimed to evaluate the effectiveness of Facebook, Twitter, and Instagram in recruiting a representative sample of pregnant women in a longitudinal pregnancy cohort study in Calgary, Alberta, between September 27, 2021, and April 24, 2022. MethodsPaid advertisements were targeted at 18- to 50-year-old women in Calgary, with interests in pregnancy. Data regarding reach, link clicks, and costs were collected through Facebook Ads Manager (Meta Platforms, Inc) and Twitter Analytics (Twitter, Inc). The feasibility of each platform for recruitment was assessed based on the recruitment rate and cost-effectiveness. The demographic characteristics of the participants recruited through each source were compared using the chi-square test. ResultsPaid advertisements reached 159,778 social media users, resulting in 2390 link clicks and 324 participants being recruited. Facebook reached and recruited the highest number of participants (153/324, 47.2%), whereas Instagram saw the highest number of link clicks relative to the number of users who saw the advertisement (418/19,764, 2.11%). Facebook and Instagram advertisements were cost-effective, with an average cost-per-click of CAD $0.65 (US $0.84; SD $0.27, US $0.35) and cost-per-completer of CAD $7.89 (US $10.25; SD CAD $4.08, US $5.30). Twitter advertisements were less successful in terms of recruitment and costs. Demographic characteristics of participants did not differ based on recruitment source, except for education and income, where more highly educated and higher-income participants were recruited through Instagram or Twitter. Many issues related to fraudulent responses were encountered throughout the recruitment period. ConclusionsPaid social media advertisements (especially Facebook and Instagram) are feasible and cost-effective methods for recruiting a large sample of pregnant women for survey-based research. However, future research should be aware of the potential for fraudulent responses when using social media for recruitment and consider strategies to mitigate this problem.